Effectiveness of bailouts in the EU - Ela Glowicka (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
Governments in the EU frequently bail out firms in distress by granting state aid. I use data from 86 cases during the years 1995-2003 to examine two issues: the effectiveness of bailouts in preventing bankruptcy and the determinants of bailout policy. The results are threefold. First, the estimated discrete-time hazard rate increases during the first four years after the subsidy and drops after that, suggesting that some bailouts only delayed exit instead of preventing it. The number of failing bailouts could be reduced if European control was tougher. Second, governments' bailout decisions favored state-owned firms, even though state-owned firms did not outperform private ones in the survival chances. Third, subsidy choice is an endogenous variable in the analysis of the hazard rate. Treating it as exogenous underestimates its impact on the bankruptcy probability. Several policy implications of the results are discussed in the paper.
urn:nbn:de:bvb:19-epub-13375-2
Keywords: K2; G3; L5; 330; State aid; European Union; Discrete-time hazard; Bivariate probit